Application of Environmental Ethics for Sustainable Development and Conservation of Saint Martins Island in Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
St. Martin is a miniature island in the north-eastern part of the Bay of Bengal, which is distinct from the Cox's Bazar-Teknaf peninsula, Bangladesh. Currentlythere are around 6000 people amidst the majority number of peoples primary livelihood sources are fishing, tourism,and agriculture.However, it has become a great tourists attraction spot in Bangladesh due to its unique landscape. Consequently, its natural environment and ecosystem, especially unique biodiversity is obliterating frequently by-virtue-of indiscriminate human activities. This problem is triggering due to lack of education and awareness. Contrary, application of environmental ethics canminimizefurther damages as-well-as rehabilitatetheisland anew. Lately, the government and some NGOs have already taken and implemented several stepsto protect the island but not fruitful still due to some drawbacks. This study reveals that population control, ecotourism, appropriatezoning system for sustainable development,introducing renewable energy, and spreading education amid mass people can resolve the dispute and resettle. Moreover, involving community people in the management program and initiating cottage industry as substitute of income sourcescan reduce pressure on island natural resources depletion.J. Environ. Sci. & Natural Resources, 8(1): 19-27 2015